Responsibility for Another’s Debt: Suretyship, Solidarity, and Imperfect Delegation - Cumyn, Michelle (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
Legal evolution is often achieved by taking a fresh look at venerable institutions whose interpretation has become thwarted, constricted, or stale. Presumptions established to protect debtors and sureties at articles 1525 and 2335 of the Civil Code of Québec have prevented jurists from borrowing freely from the rules of solidarity and suretyship. Where one person is undoubtedly responsible for the debt of another, even in the absence of a suretyship agreement, the author argues it should be possible to apply the law of suretyship by analogy. Where two persons are each liable to perform the same obligation in full, it is likewise appropriate to apply the rules of solidarity.The author’s analysis proceeds in three parts: an introduction of the basic structure of suretyship and solidarity (Part I), a discussion of important differences in the law of suretyship and solidarity (Part II), and an argument that the solidarity and suretyship models should be used to illuminate analogous complex relations where multiple persons are responsible for the same debt (Part III). More specifically, in the situation of imperfect delegation, where a person assumes liability to a creditor for payment of a debt owed by another, but the original debtor is not discharged and remains liable in case of non-payment by the new debtor, it is appropriate to apply by analogy the law of suretyship.